Sacred Scripture / Sacred Space The Interlacing of Real Places and Conceptual Spaces in Medieval Art and Architecture - Frese, Tobias (Materiale Textkulturen, 2019)
Thirteen papers on different subjects, focussing on writings and inscriptions in medieval art, explore the faculty of writing to create and determine spaces and to generate the sacred by the display of holy scripture. The subjects range from book illumination over wall painting, mosaics, sculpture, and church interiors to inscriptions on portals and façades.